Molecular and Phenotypic Characterization for Cold Tolerance in Rice (Oryza sativa L.) (Bangladesh Rice Journal, 2020)
Cold stress affects growth and development of rice plants from germination to reproductive stages. Thirty breeding lines/varieties including tolerant and susceptible check varieties were evaluated for cold tolerance at seedling and reproductive stage using artificially induced low temperature situations to understand the genetic relationship among them and to identify promising donors for cold tolerance. Three breeding lines, BR8253-9-3-4-3, IR77497-31-2-3-1and IR2266-42-6-2 demonstrated higher cold tolerance for the seedling stage (LD score